SISTEM RESERVASI TIKET BUS DI TERMINAL ARJOSARI MALANG - Wirawan, Surya; Soebroto, Arief Andy; Aknuranda, Ismiarta (MATICS, 2013)
Bus Ticket Reservation System is an application that can be used to help booking bus tickets and the buyer will get a report via SMS Gateway. The reservation system is made by conducting field studies in Arjosari Bus Station Malang. This system uses SMS Gateway to send the report to the buyer after booking bus tickets online. SMS Gateway on this application serves as a liaison which delays sms between External Short Message entitiy (ESME) and Short Message Service Center (SMSC) and so does in reserve.The reservation system made is developed with the PHP programming language and has a prototype system pattern. System functions were tested using the validation testing, performance testing, and usability testing. The results percentage of responses usability testing is 67.7%. This shows that Ticket Reservation System at Arjosari Bus Station can be used well enough. Â